2019
DOI: 10.1016/j.gaitpost.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced vestibular function is associated with longer, slower steps in healthy adults during normal speed walking

Abstract: Background: Vestibular signals contribute to balance and walking. With aging, vestibular function declines and gait speed decreases. Vestibular loss contributes to decreasing gait speed, but this influence could be linked to spatial and/or temporal aspects of gait. We investigated the relationship between vestibular function (semicircular canal and otolith function) and spatial and temporal gait parameters in a cohort of adults. Methods: 113 community-dwelling healthy adults (mean age 72.2 (14.6) years) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
(46 reference statements)
0
18
1
Order By: Relevance
“…Others have pointed to neurological deficiencies associated with slower walking, without referring to stability directly. Anson et al ( 2019 ) have shown vestibular function loss causes people to walk with longer, slower steps, contradicting findings by McCrum et al ( 2018 ) who found people with vestibular loss adapt by taking shorter, faster steps. Menz et al ( 2004 ) have shown people with peripheral neuropathy reduced walking speed and cadence.…”
Section: Introductionmentioning
confidence: 93%
“…Others have pointed to neurological deficiencies associated with slower walking, without referring to stability directly. Anson et al ( 2019 ) have shown vestibular function loss causes people to walk with longer, slower steps, contradicting findings by McCrum et al ( 2018 ) who found people with vestibular loss adapt by taking shorter, faster steps. Menz et al ( 2004 ) have shown people with peripheral neuropathy reduced walking speed and cadence.…”
Section: Introductionmentioning
confidence: 93%
“…Anson et al ( 15 ) showed that a yaw vHIT VOR gain of <0.80 bilaterally (eye velocity <80% of head velocity) was associated with greater amounts of postural sway in the eyes closed, compliant standing (i.e., foam) condition of the MRBT. Anson and colleagues subsequently showed that for every 0.1 decrease in VOR gain, the likelihood of failing (i.e., falling prior to 40 s) this same test increased by 8% ( 58 ). Compared to the low frequency range of calorics and rotational chair testing, the high frequency content (1–6 Hz) of impulsive testing provides a stimulus to the vestibular system that is more representative of the demands of typical human locomotion [0.8–3.2 Hz ( 51 )], providing a potential explanation for its superior association with balance impairments among older adults ( 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gait is an essential body function for activities of daily living. During acute stage, individuals with uVN have deterioration in gait function because the vestibular dysfunction elicit static and dynamic de cit in posture and balance control during gait 2,4,5 . After acute stage, the dynamic de cit of vestibular function considerably persists while static de cit almost disappears 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Because gait is a complex body function related with vestibulo ocular re ex (VOR), vestibular spinal re ex (VS), reticulo spinal re ex, cerebellum and higher cortical functions, severity of vestibular dysfunction has limitations in predicting gait disturbances after uVN. Although dysfunction of the VOR is an underpinning of symptoms in uVN, there is con icting evidence regarding the relationship between VOR recovery and gait function 5 . Weak correlations between VOR and gait function suggest that gait function should be evaluated independently of VOR recovery 7 .…”
Section: Introductionmentioning
confidence: 99%